Міграційна політика та міграційні процеси в Україні - Сафонов, Юрій Миколайович (My University, 2015)
У статті розглянуто міграційні процеси. В умовах зростаючої глобалізації та розширення світових економічних відносин ці процеси поглиблюються. Оптимізація міграційних потоків є важливим завданням подальшого успішного соціально- економічного розвитку держави. Розглянуто державну міграційну політику України. The article describes the migration process. In a globalized world economy labor migration plays a leading role among the forms of international economic relations. Influenced by the intensification of production processes, the spread of new technologies, internationalization of financial flows, restructuring of national economies, due to scientific, technical and information and communications revolution labor migration affects all processes in the society and generates significant economic, political, social, natural problems, but also promotes the balancing of public relations, elimination of social tension, realizing the human right to a free life and work in the country where it can bring a significant contribution to world production and their own welfare. In an increasingly globalized world and the expansion of economic relations these processes are deepened. Optimization of migratory flows is a critical objective of further successful social and economic development of the state. The state migration policy is considered.
Keywords: міграція; міграційна політика; міграційні процеси; державне регулювання; кафедра міжнародної економіки